Three new monoterpene glucosides from Sibiraea angustata. Issue 21 (1st November 2016) - Yao, Zhengzheng; Liu, Hongdong; Xu, Xianghong; Chen, Xiaotian; Zhang, Dongming; Lai, Xuewen; Xu, Peng; Li, Bin
Abstract: Three new monoterpene glycosides, named sibiraglycoside I(1 ), J(2 ) and K(3 ), were isolated from an aqueous extract of the aerial portion of Sibiraea angustata. Their structures were elucidated on the basis of extensive spectroscopic data analysis (including 1D and 2D NMR and MS experiments) and compared to literature data. Abstract : Three new monoterpene glucosides were isolated and identified from the plant of Sibiraea angustata .